Global research on cancer and sleep: A bibliometric and visual analysis of the last two decades - Sun, Jiaru; Wang, Caihua; Hui, Zhaozhao; Han, Wenjin; Wang, Xiaoqin; Wang, Mingxu (Frontiers in Neurology, 2023)
Objective The study aimed to analyze the research status, hotspots, and frontiers of global research on cancer and sleep through bibliometrics and provide references and guidance for future research. Methods The literature regarding cancer and sleep from 2002 to 2022 was searched from the Web of Science Core Collection (WoSCC) database. CiteSpace 5.6.R3 was performed for visualization analysis. Results A total of 1,172 publications were identified. The number of publications in the field has gradually increased over the past two decades. The United States had the most prominent contributions. Taipei Medical University and the University of California, San Francisco, and David Gozal were the most prolific institutions and author, respectively. The most published academic journal was Supportive Care in Cancer. The research hotspots can be summarized into the symptom cluster intervention for cancer survivors and the association between cancer and melatonin and/or obstructive sleep apnea (OSA). The complex interaction between cancer and sleep disruption and the influencing factors of sleep quality may be the emerging trends of research. Conclusion This study systematically analyzed the hotspots and frontiers in the field of cancer and sleep and called for strengthening cooperation among countries, institutions, and authors. In addition, intervention measures for the cancer symptom cluster, the bioavailability of exogenous melatonin, the causal relationship between OSA and cancer, the mechanism of tumor-induced sleep disruption, the dose–response relationship between sleep duration and cancer risk, and the path relationship between sleep quality influencing factors may be the focus of future research.